Optimization of microwave assisted Maillard reaction to fabricate and evaluate corn fiber gum-chitosan IPN films. (February 2015) - Kamboj, Sunil; Singh, Kuldeep; Tiwary, A.K.; Rana, Vikas
Abstract: The aim of this study was to optimize and characterize microwave assisted Maillard reaction between corn fiber gum (CFG) and chitosan (CH) using 3 3 full factorial design. Browning intensity, surface free energy components, mechanical properties, thermal attributes, electrical performance, water vapor permeability (WVP), solvent interaction behavior and antimicrobial activity were evaluated. The Maillard reaction product of CFG:CH showed shear thinning behavior. The enhancement in the dispersive components of surface free energy indicated Maillard reaction created water resistance in the films. The films were mechanically strong and flexible. The physicochemical descriptors reflected Maillard reaction produces strong interpenetrating polymer network (IPN) that leads to production of films resistant to water, acids and alkali. This was also observed in SEM analysis. In addition, the enhancement in zones of inhibition suggested antibacterial activity of Maillard reaction product. Overall, the films (F21) produced via Maillard reaction "in situ" were tough, flexible, water resistant and antimicrobial in nature. Thus, suggested high potential of these IPN films in food and pharmaceuticals. Graphical abstract: Highlights: Microwave assisted method was used to synthesize MRPs employing optimization technique. MRP synthesis correlated with browning intensity and surface free energy components. Rheological, textural and mechanical performance of MRPs were enhanced. MRP films were acid & alkali resistant with increased dispersive component. The antibacterial activity of MRP was 5 fold enhanced with respect to control.